Biodegradation and hydrolysis rate of aliphatic aromatic polyester - Kijchavengkul, Thitisilp; Auras, Rafael; Rubino, Maria; Selke, Susan; Ngouajio, Mathieu; Fernandez, R. Thomas (Polymer degradation and stability, 2010)
The biodegradation and hydrolysis rates of an aliphatic aromatic copolyester were measured in manure, food, and yard compost environments and in phosphate buffer solution (pH = 8.0) and vermiculite at 58 °C. Mineralization, molecular weight reduction, and structural changes determined by DSC, FTIR, and 1H NMR were used as indicators of the biodegradation and hydrolysis rates. Poly(butylene adipate- co-terephthalate), PBAT, film biodegraded at distinctive rates in manure, food, and yard compost environments having different microbial activities. The highest biodegradation rate was found in manure compost, which had the highest CO 2 emissions and lowest C/N ratio. The possible presence of extracellular enzymes in manure and food composts may facilitate the hydrolytic reaction since greater molecular weight reduction rates were observed in these composts. 1H NMR and thermal analysis revealed that, while PBAT is a semi-crystalline copolyester with cocrystallization of BT and BA dimers, the soft aliphatic domain (BA) and the amorphous region are more susceptible to hydrolysis and biodegradation than the rigid aromatic domain (BT) and the crystalline region.